Impact of demographic factors on consumer behaviour in the organized and unorganized retail sector - Cheshta Kashyap,; Chopra, Nancy (IJRDO - Journal of Business Management, 2018)
In the present scenario of fast changing lifestyle (preferences and taste) of consumer both unorganized retail outlets and organized retail outlets should be more revolutionary in order to survive, retain and attract new customers. There are various key drivers that lead to the retailing industry as a next booming industry like: value added goods sales, rising aspirations, favorable demographics, increasing population of women, food and apparel etc. Driven by the need to compete in volatile market places and to maximize profits it has become mandatory for the retailers to layout their stores in the way that will attract their potential customers and helps in maintaining the loyalty of the present customers (Das.K and Tripathy.P 2015). This paper provides insight into impact of demographic factors on the buying behaviour of the consumers between organized and unorganized retail sectors. The paper also focuses on suggesting some ways for improving the satisfaction level of customers of both organized and unorganized retail outlets.